Efficient and equitable allocation of renewable portfolio standards targets among China's provinces. (February 2019) - Wang, Ge; Zhang, Qi; Li, Yan; Mclellan, Benjamin C.
Abstract: Allocating the Renewable Portfolio Standard (RPS) targets among provinces in an economically viable and fair way is the first critical step to implementing the RPS policy in China. To explore this issue, a cost minimizing model was proposed and applied in this paper. The least-cost 2018 – 2020 RPS target allocation scheme for 29 provinces and regions in China was obtained. The efficiency and equity of the RPS target allocation scheme published by China National Energy Administration in 2018 was compared with the obtained least-cost scheme and an equal allocation scheme referring to the practice in countries with only national RPS target from three aspects – energy, environment and economy. The results showed that: (1) the least-cost scheme can reduce the total cost by 3% while increasing the distribution inequity of non-hydro renewable electricity consumption measured by the Gini coefficient by 343% (112% if hydro is included); (2) the equally-allocated scheme did not show a significant advantage in equity over the government published scheme but increased the cost. Based on the results, the possibility of adopting a national renewable energy certificates trade market to reduce the cost while maintaining the equity has been discussed, and the relevant policy suggestions have been proposed. Highlights: A China provincial RPS target allocation model was presented. A least-cost RPS target allocation scheme was obtained. 3E analyses on the efficiency and equity of the schemes were conducted. The least-cost scheme produces lower cost and equity than the government one. The equal-allocated scheme did not show significant advantages in equity.